Preparation method of graphene metal heat-conducting gasket
Through the method of processing plasma treatment of graphene and depositing nanoparticles at the metal base, the problem of poor combination of graphene and metal, significantly improved thermal conductivity and antioxidant capacity, and meet the demand for high -efficiency heat dissipation materials for electronic equipment Essence
Patent Information
- Application Number
- CN202411477520.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
The existing preparation technology of graphene metal thermal conductivity gaskets is difficult to ensure sufficient and uniform bond between graphene and metal, resulting in large interface thermal resistance, poor thermal conductivity, and difficult to control the distribution and orientation of graphene.
By plasma treatment of graphene, active functional groups are introduced, and nanoparticles are deposited on the surface of the metal substrate to improve the bonding strength. At the same time, low-temperature hot-pressing composite technology and anti-oxidation coating treatment are used to enhance thermal conductivity and anti-oxidation capabilities.
It significantly improves the bonding strength between graphene and metal, reduces interface thermal resistance, improves thermal conductivity and oxidation resistance, extends the service life of equipment, and reduces material costs.
Smart Images

Figure BDA0005096507650000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat-conducting material preparation, and in particular to a method for preparing a graphene metal heat-conducting gasket. Background Art
[0002] In today's wave of technological development, the performance of electronic devices continues to improve, and their operating speed and integration are increasing. However, this progress has also brought a severe challenge - the heat dissipation problem. Efficient heat dissipation is essential to ensure the stable operation of electronic equipment, extend its service life and achieve optimal performance. Thermal pads, as a key thermal management material, play an indispensable role in the heat dissipation system of electronic equipment.
[0003] At present, in the field of preparation of graphene metal thermal conductive gaskets, existing technical methods often find it difficult to ensure sufficient and uniform bonding between graphene and metal. This results in a large interface thermal resistance between the two in practical applications, which seriously weakens the overall thermal conductivity of the thermal conductive gasket. There are also difficulties in controlling the distribution and orientation of graphene, making it impossible to form an ideal thermal conductive channel, thereby limiting the efficiency of heat transfer.
[0004] In summary, the existing preparation technology of graphene metal thermal conductive gaskets has many problems in bonding effect and thermal conductivity, and cannot meet the growing demand of the electronic equipment industry for efficient heat dissipation materials. Therefore, developing an innovative preparation method of graphene metal thermal conductive gaskets that can overcome these defects has extremely important practical significance and broad application prospects. Summary of the invention
[0005] Technical issues solved
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing a graphene metal thermal conductive gasket. Through plasma treatment of graphene and special treatment of the metal substrate, the interfacial thermal resistance is greatly reduced, heat transfer is made more efficient, and dependence on expensive equipment and complex operations is reduced. The low-temperature hot pressing process is energy-saving and efficient, and the optimized selection of raw materials reduces material costs. In view of the problem that traditional products are susceptible to oxidation and corrosion, the surface anti-oxidation coating used in the present invention can effectively resist harsh environments and maintain stable performance even under extreme conditions such as high temperature and high humidity, thereby reducing equipment maintenance costs and potential environmental hazards.
[0007] Technical Solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] A method for preparing a graphene metal thermally conductive gasket, the specific steps of the preparation method are:
[0010] S1. Pretreatment of graphene:
[0011] S1.1. Raw material selection and dispersion: Select high-purity graphite powder as the raw material, weigh it accurately, and disperse it in an organic solvent containing a specific surfactant;
[0012] S1.2, ultrasonic exfoliation treatment: placing the above mixed solution in a high-power ultrasonic generator, during which the energy of the ultrasonic wave effectively overcomes the van der Waals force between graphite layers, causing the graphite sheets to gradually exfoliate into graphene sheets;
[0013] S1.3, centrifugal separation and purification: centrifuge the solution after ultrasonic treatment at 6000 rpm for 90 minutes, and collect the supernatant, i.e. the graphene suspension with fewer layers, thinner thickness and higher quality;
[0014] S2. Plasma treatment of graphene:
[0015] S2.1. Equipment selection and preparation: Use plasma treatment equipment to perform plasma treatment on the obtained graphene to introduce active functional groups on its surface;
[0016] S2.2, gas configuration and introduction: argon and oxygen are mixed according to the volume ratio, used as the processing gas, and introduced into the processing equipment at a certain flow rate;
[0017] S2.3, processing parameter setting: control the plasma power at 150W, and set the processing time to 12 minutes;
[0018] S2.4, Surface modification: Under the bombardment of high-energy particles in plasma, abundant chemically active sites are generated on the graphene surface, which are compatible with metals, and the distribution and density of its surface active functional groups are evaluated;
[0019] S3. Preparation of metal substrate:
[0020] S3.1. Substrate material selection: Use high-purity copper foil as the metal substrate;
[0021] S3.2, surface cleaning treatment: put the copper foil into acetone, ethanol and deionized water in turn, and use ultrasonic cleaning to remove grease, dust and impurities on the surface of the copper foil;
[0022] S3.3, Activation treatment: Activate the cleaned copper foil with a dilute sulfuric acid solution to make the copper foil surface more reactive;
[0023] S4. Nanoparticle deposition on metal substrates:
[0024] S4.1. Preparation of electrolyte: prepare 0.05 mol / L silver nitrate electrolyte to make the electrolyte composition uniform and stable;
[0025] S4.2, electrochemical deposition parameter setting: control the current density, the deposition time is 15 minutes;
[0026] S4.3, Nanoparticle formation: Through electrochemical deposition, uniformly distributed, fine-sized silver nanoparticles are formed on the surface of the copper foil, which significantly increases the surface roughness of the metal substrate and provides more contact sites;
[0027] S5. Composite of graphene and metal substrate:
[0028] S5.1. Graphene suspension spraying: using high-precision spray equipment, the pre-treated graphene suspension is evenly sprayed on the metal substrate;
[0029] S5.2, interface enhancement layer formation: a layer of interface enhancement material layer is formed on the graphene layer by spin coating, the interface enhancement material layer is made of a solution containing a nano-scale silane coupling agent to improve its bonding strength
[0030] S5.3, drying treatment: forming an interface reinforcement material layer on the graphene layer by spin coating, the interface reinforcement material layer is made of a solution containing a nano-scale silane coupling agent, and placing the sprayed sample in a drying oven to remove the solvent so that the graphene is firmly attached to the metal substrate;
[0031] S5.4, low temperature hot pressing composite: using hot pressing equipment, under the protection of nitrogen, the graphene is brought into close contact with the metal substrate, physical and chemical interactions occur, and a strong bonding interface is formed;
[0032] S6. Post-processing:
[0033] S6.1 Annealing: Anneal the composite gasket in a vacuum annealing furnace with a vacuum degree of 10 -3 Pa, annealing temperature is 400℃, time is 1 hour. During the annealing process, the diffusion and rearrangement of atoms can eliminate the residual stress inside the material;
[0034] S6.2. Anti-oxidation coating: Silicon nitride is selected as the anti-oxidation coating material, and the coating method is sprayed to control the thickness of the coating to 5μm to prevent the gasket from oxidation and corrosion in harsh environments and extend its service life.
[0035] Furthermore, the organic solvent selected in S1.1 is N-methylpyrrolidone NMP, and the surfactant is sodium dodecylbenzene sulfonate, and the concentration thereof is controlled at 2 wt %.
[0036] Furthermore, in S1.2, 10 g of high-quality graphite powder is uniformly dispersed in 1000 ml of N-methylpyrrolidone (NMP) solution containing 5 wt% sodium dodecylbenzene sulfonate, and ultrasonically treated at a frequency of 20 kHz and 40 W / cm 2 The ultrasonic treatment is performed with an amplitude of 1000 nm and the ultrasonic time is 3-6 hours to fully exfoliate the graphite powder into graphene sheets.
[0037] Furthermore, the S2.1 performs plasma treatment on the obtained graphene to introduce active functional groups on its surface. The treatment gas is a mixed gas of argon and oxygen with a volume ratio of 9:1. During the treatment, the plasma power is controlled at 200 W and the treatment time is 15 minutes. The high-energy particles of the plasma bombard the surface of the graphene to produce chemically active sites, thereby enhancing the compatibility with the metal and laying the foundation for subsequent good bonding with the metal.
[0038] Furthermore, the plasma treatment of the S2 graphene further comprises:
[0039] S2.5, Plasma excitation method: A unique plasma excitation method, namely pulse power excitation, is used to generate more active plasma, making the interaction between plasma and graphene more intense, thereby improving the effect of surface modification;
[0040] S2.6. Multi-stage plasma treatment: Design a multi-stage plasma treatment process and adjust the gas ratio, power and treatment time parameters at different stages.
[0041] Furthermore, the specific parameters of different stages of the S2.6 multi-stage plasma treatment are adjusted as follows:
[0042] The first stage, pretreatment: the gas volume ratio of argon and oxygen was set to 8:2, the power was set to 100W, and the treatment time lasted for 5 minutes to perform preliminary activation on the graphene surface;
[0043] The second stage, deep treatment: the gas volume ratio of argon and oxygen is adjusted to 9:1, the power is adjusted to 150W, and the treatment time is extended to 7 minutes to introduce more active functional groups to make the graphene surface active and compatible with metals;
[0044] The third stage is stabilization treatment: the gas ratio of argon and oxygen is maintained at 9:1, the power is reduced to 120W, and the treatment time lasts for 5 minutes. The stabilization treatment is used to consolidate the effect of surface modification and ensure the stable existence of active functional groups, while avoiding adverse effects of excessive treatment on the graphene structure.
[0045] Furthermore, the S3.1 uses high-purity copper foil as the metal substrate, performs surface cleaning on the copper foil, and uses acetone, ethanol and deionized water for ultrasonic cleaning in sequence, with each solvent ultrasonic cleaning time being 15 minutes. The cleaned copper foil is activated using a 5% dilute hydrochloric acid solution for 10 minutes to make the copper foil surface have higher reactivity.
[0046] Furthermore, during the nanoparticle deposition process of the S4 metal substrate, a layer of nanoscale metal particles is deposited on the surface of the copper foil by an electrochemical method, using a 0.05-0.1 mol / L silver nitrate electrolyte and controlling the current density to be 0.1-0.5 A / dm 2 The deposition time is 25 minutes, and uniformly distributed, small-sized silver nanoparticles are formed on the surface of the copper foil. These nanoparticles can increase the surface roughness of the metal substrate, thereby providing more contact sites and increasing the contact area with graphene.
[0047] Furthermore, the S5 evenly sprays the pretreated graphene suspension on the metal substrate, using high-precision spray equipment to control the spray pressure to 0.3MPa, the flow rate to 5ml / min and the angle to 45°, so that the graphene suspension can evenly cover the surface of the metal substrate, and the sprayed sample is placed in a drying oven for drying, the drying temperature is controlled at 100°C, and the drying time is 2 hours to remove the solvent so that the graphene is firmly attached to the metal substrate.
[0048] Furthermore, the S5.4 adopts a low-temperature hot pressing process to composite the graphene with the metal substrate under the protection of an inert gas. During the hot pressing process, high-purity nitrogen is introduced to prevent the graphene and the metal from oxidizing at high temperatures. The pressure is controlled at 10 MPa. By applying uniform pressure, the graphene is in close contact with the metal substrate. The temperature is controlled at 250°C for 1.5 hours.
[0049] Beneficial Effects
[0050] Compared with the prior art, the technical solution provided by the present invention has the following advantages:
[0051] Beneficial effects:
[0052] 1. The present invention greatly improves the bonding strength between graphene and metal by plasma treatment of graphene and deposition of nanoparticles on the surface of metal substrate, effectively reduces the interfacial thermal resistance, enables heat to be transferred more smoothly between graphene and metal, and enables the heat generated by electronic equipment during operation to be conducted away more quickly, effectively avoiding the problem of local overheating, greatly improving the stability and reliability of the equipment, and extending its service life.
[0053] 2. The present invention significantly enhances the anti-oxidation and anti-corrosion capabilities of the gasket by coating a layer of anti-oxidation coating on the surface of the gasket, and can maintain stable performance even in harsh environments such as high temperature and high humidity. This improvement in stability not only reduces the frequency and cost of equipment maintenance, but also broadens the application scope of the thermally conductive gasket. Whether in extreme industrial environments or inside complex electronic equipment, the thermally conductive gasket prepared by the present invention can work reliably. At the same time, the use of the coating also reduces potential harm to the environment. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the present invention is described clearly and completely. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] The present invention will be further described below in conjunction with the embodiments.
[0056] Embodiment 1
[0057] This embodiment describes in detail the specific process of a method for preparing a graphene metal thermal conductive gasket, and displays in detail the specific preparation parameters and performance test data to verify the effectiveness and superiority of the invention.
[0058] Pretreatment of graphene: 10 g of high-purity graphite powder was selected as the raw material, accurately weighed, and dispersed in 1000 ml of an organic solvent of N-methylpyrrolidone containing 2 wt% sodium dodecylbenzene sulfonate. The mixed solution was placed in a high-power ultrasonic generator at a frequency of 20 kHz and 40 W / cm 2 The mixture was ultrasonically treated for 4 hours at an amplitude of 1000 rpm, centrifuged at 6000 rpm for 90 minutes, and the supernatant was collected to obtain a graphene suspension with fewer layers, thinner thickness and higher quality.
[0059] Plasma treatment of graphene: Select plasma treatment equipment and set the treatment parameters for different stages. That is, argon and oxygen are mixed in a volume ratio of 9:1, and introduced into the treatment equipment at a flow rate of 10L / min. The plasma power is controlled at 200W and the treatment time is set to 15 minutes. Under the bombardment of high-energy plasma particles, abundant chemically active sites are generated on the surface of graphene, enhancing its compatibility with metals.
[0060] Preparation of metal substrate: Use high-purity copper foil with a purity of 99.99% as the metal substrate. The size of the copper foil is 10cm×10cm. Put the copper foil into acetone, ethanol and deionized water in turn. Ultrasonic cleaning is performed for 15 minutes in each solvent. The cleaned copper foil is activated with a 5% dilute hydrochloric acid solution for 10 minutes.
[0061] Nanoparticle deposition on metal substrate: Prepare 500 ml of 0.05 mol / L silver nitrate electrolyte and control the current density at 0.3 A / dm 2 The deposition time is 25 minutes, and uniformly distributed and fine-sized silver nanoparticles are formed on the surface of the copper foil.
[0062] Composite of graphene and metal substrate: Using high-precision spray equipment, control the spray pressure to 0.3MPa, the flow rate to 5ml / min and the angle to 45°, spray the pretreated graphene suspension evenly on the metal substrate, place the sprayed sample in a drying oven at 100°C for 2 hours, and use hot pressing equipment, under the protection of high-purity nitrogen (purity 99.999%), control the pressure to 10MPa, the temperature to 250°C, and hot press for 1.5 hours.
[0063] Post-processing: Place the composite gasket in a vacuum annealing furnace and the vacuum degree reaches 10 -3 Pa, annealed at 400°C for 1 hour, silicon nitride was selected as the anti-oxidation coating material, and the coating was sprayed to control the coating thickness to 5 μm.
[0064] The performance test of the graphene metal thermal conductive gasket prepared in this embodiment showed that the thermal conductivity was 500 W / m·K, the bonding strength was 25 MPa, and the anti-oxidation performance was excellent.
[0065] Embodiment 2
[0066] Pretreatment of graphene: 10 g of high-purity graphite powder was selected as the raw material, accurately weighed, and dispersed in 1000 ml of an organic solvent of N-methylpyrrolidone containing 2 wt% sodium dodecylbenzene sulfonate. The mixed solution was placed in a high-power ultrasonic generator at a frequency of 20 kHz and 40 W / cm 2 The mixture was ultrasonically treated for 5 hours at an amplitude of 1000 rpm, centrifuged at 8000 rpm for 60 minutes, and the supernatant was collected to obtain a graphene suspension with fewer layers, thinner thickness and higher quality.
[0067] Plasma treatment of graphene: Select plasma treatment equipment and set the treatment parameters for different stages. That is, argon and oxygen are mixed in a volume ratio of 8:2, and introduced into the treatment equipment at a flow rate of 10L / min. The plasma power is controlled at 200W and the treatment time is set to 15 minutes. Under the bombardment of high-energy plasma particles, abundant chemically active sites are generated on the surface of graphene, enhancing its compatibility with metals.
[0068] Preparation of metal substrate: Use high-purity copper foil with a purity of 99.99% as the metal substrate. The size of the copper foil is 10cm×10cm. Put the copper foil into acetone, ethanol and deionized water in turn. Ultrasonic cleaning is performed for 15 minutes in each solvent. The cleaned copper foil is activated with a 3% dilute hydrochloric acid solution for 15 minutes.
[0069] Nanoparticle deposition on metal substrate: Prepare 500 ml of 0.1 mol / L silver nitrate electrolyte and control the current density at 0.5 A / dm 2 The deposition time is 20 minutes, and uniformly distributed and fine-sized silver nanoparticles are formed on the surface of the copper foil.
[0070] Composite of graphene and metal substrate: Using high-precision spray equipment, control the spray pressure to 0.3MPa, flow rate to 5ml / min and angle to 45°, spray the pretreated graphene suspension evenly on the metal substrate, place the sprayed sample in a drying oven at 100°C for 2 hours, use hot pressing equipment, under the protection of high-purity nitrogen (purity 99.999%), control the pressure to 10MPa, the temperature to 280°C, and hot press for 1 hour.
[0071] Post-processing: Place the composite gasket in a vacuum annealing furnace and the vacuum degree reaches 10 -3 Pa, annealed at 350°C for 1.5 hours, silicon nitride was selected as the anti-oxidation coating material, and the coating was sprayed to control the coating thickness to 5 μm.
[0072] The performance test of the graphene metal thermal conductive gasket prepared in this embodiment showed that the thermal conductivity was 480 W / m·K, the bonding strength was 23 MPa, and the anti-oxidation performance was good.
[0073] Embodiment 3
[0074] Pretreatment of graphene: 15 g of high-purity graphite powder was selected as the raw material, accurately weighed, and dispersed in 1500 ml of an organic solvent of N-methylpyrrolidone containing 2 wt% sodium dodecylbenzene sulfonate. The mixed solution was placed in a high-power ultrasonic generator at a frequency of 20 kHz and 40 W / cm 2The mixture was ultrasonically treated for 3 hours at an amplitude of 1000 rpm, centrifuged at 6000 rpm for 90 minutes, and the supernatant was collected to obtain a graphene suspension with fewer layers, thinner thickness and higher quality.
[0075] Plasma treatment of graphene: Select plasma treatment equipment and set the treatment parameters for different stages. That is, argon and oxygen are mixed in a volume ratio of 9:1, and introduced into the treatment equipment at a flow rate of 10L / min. The plasma power is controlled at 180W and the treatment time is set to 10 minutes. Under the bombardment of high-energy plasma particles, abundant chemically active sites are generated on the surface of graphene, enhancing its compatibility with metals.
[0076] Preparation of metal substrate: Use high-purity copper foil with a purity of 99.99% as the metal substrate. The size of the copper foil is 15cm×15cm. Put the copper foil into acetone, ethanol and deionized water in turn. Ultrasonic cleaning is performed for 15 minutes in each solvent. The cleaned copper foil is activated with a 5% dilute hydrochloric acid solution for 10 minutes.
[0077] Nanoparticle deposition on metal substrate: Prepare 500 ml of 0.08 mol / L silver nitrate electrolyte and control the current density at 0.4 A / dm 2 The deposition time is 30 minutes, and uniformly distributed and fine-sized silver nanoparticles are formed on the surface of the copper foil.
[0078] Composite of graphene and metal substrate: Using high-precision spray equipment, control the spray pressure to 0.3MPa, the flow rate to 5ml / min and the angle to 45°, spray the pretreated graphene suspension evenly on the metal substrate, place the sprayed sample in a drying oven at 100°C for 2 hours, and use hot pressing equipment, under the protection of high-purity nitrogen (purity 99.999%), control the pressure to 8MPa, the temperature to 220°C, and hot press for 2 hours.
[0079] Post-processing: Place the composite gasket in a vacuum annealing furnace and the vacuum degree reaches 10 -3 Pa, annealed at 380°C for 0.5 hour, silicon nitride was selected as the anti-oxidation coating material, and the coating was sprayed to control the coating thickness to 5 μm.
[0080] The performance test of the graphene metal thermal conductive gasket prepared in this embodiment showed that the thermal conductivity was 52 W / m·K, the bonding strength was 26 MPa, and the anti-oxidation performance was excellent.
[0081] Embodiment 4
[0082] Graphene pretreatment: 8 g of high-purity graphite powder was selected as the raw material, accurately weighed, and dispersed in 800 ml of N-methylpyrrolidone organic solvent containing 1.5 wt% sodium dodecylbenzene sulfonate. The mixed solution was placed in a high-power ultrasonic generator at a frequency of 20 kHz and 35 W / cm 2 The mixture was ultrasonically treated for 4.5 hours at an amplitude of 1000 rpm, centrifuged at 7000 rpm for 75 minutes, and the supernatant was collected to obtain a graphene suspension with fewer layers, thinner thickness and higher quality.
[0083] Plasma treatment of graphene: Select plasma treatment equipment and set the treatment parameters for different stages. That is, argon and oxygen are mixed in a volume ratio of 9:1, and introduced into the treatment equipment at a flow rate of 8L / min. The plasma power is controlled at 180W and the treatment time is set to 12 minutes. Under the bombardment of high-energy plasma particles, abundant chemically active sites are generated on the surface of graphene, enhancing its compatibility with metals.
[0084] Preparation of metal substrate: Use high-purity copper foil with a purity of 99.99% as the metal substrate. Its size is 12cm×12cm. Put the copper foil into acetone, ethanol and deionized water in turn. Ultrasonic clean each solvent for 12 minutes. Activate the cleaned copper foil with a 5% dilute hydrochloric acid solution for 12 minutes.
[0085] Nanoparticle deposition on metal substrate: Prepare 400 ml of 0.06 mol / L silver nitrate electrolyte and control the current density at 0.25 A / dm 2 The deposition time is 22 minutes, and uniformly distributed and fine-sized silver nanoparticles are formed on the surface of the copper foil.
[0086] Composite of graphene and metal substrate: Using high-precision spray equipment, control the spray pressure to 0.25MPa, the flow rate to 4ml / min and the angle to 40°, and evenly spray the pretreated graphene suspension on the metal substrate. Place the sprayed sample in a drying oven at 90°C for 1.5 hours, and use hot pressing equipment. Under the protection of high-purity nitrogen (purity 99.999%), the pressure is controlled at 9MPa, the temperature is controlled at 240°C, and hot pressing is performed for 1.2 hours.
[0087] Post-processing: Place the composite gasket in a vacuum annealing furnace and the vacuum degree reaches 10 -3 Pa, annealed at 380°C for 0.8 hours, silicon nitride was selected as the anti-oxidation coating material, and the coating was sprayed to control the coating thickness to 4.5 μm.
[0088] The performance test of the graphene metal thermal conductive gasket prepared in this embodiment showed that the thermal conductivity was 490 W / m·K, the bonding strength was 24 MPa, and the anti-oxidation performance was good.
[0089] Embodiment 5
[0090] Pretreatment of graphene: 12 g of high-purity graphite powder was selected as the raw material, accurately weighed, and dispersed in 1200 ml of an organic solvent of N-methylpyrrolidone containing 2.5 wt% sodium dodecylbenzene sulfonate. The mixed solution was placed in a high-power ultrasonic generator at a frequency of 20 kHz and 45 W / cm 2 The mixture was ultrasonically treated at an amplitude of 5.5 hours, centrifuged at 5500 rpm for 100 minutes, and the supernatant was collected to obtain a graphene suspension with fewer layers, thinner thickness and higher quality.
[0091] Plasma treatment of graphene: Select plasma treatment equipment and set the treatment parameters for different stages. That is, argon and oxygen are mixed in a volume ratio of 9:1, and introduced into the treatment equipment at a flow rate of 12L / min. The plasma power is controlled at 220W and the treatment time is set to 18 minutes. Under the bombardment of high-energy plasma particles, abundant chemically active sites are generated on the surface of graphene, enhancing its compatibility with metals.
[0092] Preparation of metal substrate: Use high-purity copper foil with a purity of 99.99% as the metal substrate. Its size is 13cm×13cm. Put the copper foil into acetone, ethanol and deionized water in turn. Ultrasonic cleaning is performed for 18 minutes in each solvent. The cleaned copper foil is activated with a 5% dilute hydrochloric acid solution for 8 minutes.
[0093] Nanoparticle deposition on metal substrate: Prepare 600 ml of 0.09 mol / L silver nitrate electrolyte and control the current density at 0.45 A / dm 2 The deposition time is 28 minutes, and uniformly distributed and fine-sized silver nanoparticles are formed on the surface of the copper foil.
[0094] Composite of graphene and metal substrate: Using high-precision spray equipment, control the spray pressure to 0.35MPa, the flow rate to 6ml / min and the angle to 50°, and evenly spray the pretreated graphene suspension on the metal substrate. Place the sprayed sample in a drying oven at 110°C for 2.5 hours. Using hot pressing equipment, under the protection of high-purity nitrogen (purity 99.999%), control the pressure at 11MPa, the temperature at 260°C, and hot press for 1.8 hours.
[0095] Post-processing: Place the composite gasket in a vacuum annealing furnace and the vacuum degree reaches 10 -3Pa, annealed at 420°C for 1.2 hours, silicon nitride was selected as the anti-oxidation coating material, and the coating was sprayed to control the coating thickness to 5.5 μm.
[0096] The performance test of the graphene metal thermal conductive gasket prepared in this embodiment showed that the thermal conductivity was 510 W / m·K, the bonding strength was 25.5 MPa, and the anti-oxidation performance was excellent.
[0097] Comparative Example
[0098] A conventional method for preparing a graphene metal thermally conductive gasket is adopted, that is, the graphene is not subjected to plasma treatment, nanoparticles are not deposited on the metal substrate, and other steps are the same as those in the first embodiment.
[0099] The specific results are as follows:
[0100]
[0101] As described in the above table, the following conclusions were drawn through the performance tests of the graphene metal thermally conductive pads prepared in Examples 1 to 5 and the comparative example:
[0102] In terms of thermal conductivity, Examples 1 to 5 are significantly higher than the comparative example, among which Example 3 has the highest thermal conductivity, reaching 520 W / m·K, indicating that the preparation method of the present invention can significantly improve the thermal conductivity of the thermally conductive gasket.
[0103] In terms of bonding strength, the embodiments are also better than the comparative examples. The bonding strengths of embodiments one to five are between 23 MPa and 26 MPa, which is significantly improved compared to 18 MPa of the comparative example, indicating that the preparation process of the present invention helps to enhance the bonding between graphene and the metal substrate.
[0104] In terms of antioxidant performance, Examples 1 to 5 performed well, all of which were excellent and good, while the comparative example was only average, proving that the post-processing steps of the present invention, including annealing and antioxidant coating coating, effectively improved the antioxidant capacity of the thermal pad and extended its service life.
[0105] In general, compared with traditional methods, the preparation method of a graphene metal thermal conductive gasket of the present invention has significant advantages in thermal conductivity, bonding strength and anti-oxidation performance, and can meet the higher requirements of electronic equipment for efficient heat dissipation materials.
[0106] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a graphene metal thermally conductive pad, characterized in that: The specific steps of the preparation method are: S1. Pretreatment of graphene: S1.
1. Raw material selection and dispersion: Select high-purity graphite powder as the raw material, weigh it accurately, and disperse it in an organic solvent containing a specific surfactant; S1.2, ultrasonic exfoliation treatment: placing the above mixed solution in a high-power ultrasonic generator, during which the energy of the ultrasonic wave effectively overcomes the van der Waals force between graphite layers, causing the graphite sheets to gradually exfoliate into graphene sheets; S1.3, centrifugal separation and purification: centrifuge the solution after ultrasonic treatment at 6000 rpm for 90 minutes, and collect the supernatant, i.e. the graphene suspension with fewer layers, thinner thickness and higher quality; S2. Plasma treatment of graphene: S2.
1. Equipment selection and preparation: Use plasma treatment equipment to perform plasma treatment on the obtained graphene to introduce active functional groups on its surface; S2.2, gas configuration and introduction: argon and oxygen are mixed according to the volume ratio, used as the processing gas, and introduced into the processing equipment at a certain flow rate; S2.3, processing parameter setting: control the plasma power at 150W, and set the processing time to 12 minutes; S2.4, Surface modification: Under the bombardment of high-energy particles in plasma, abundant chemically active sites are generated on the graphene surface, which are compatible with metals, and the distribution and density of its surface active functional groups are evaluated; S3. Preparation of metal substrate: S3.
1. Substrate material selection: Use high-purity copper foil as the metal substrate; S3.2, surface cleaning treatment: put the copper foil into acetone, ethanol and deionized water in turn, and use ultrasonic cleaning to remove grease, dust and impurities on the surface of the copper foil; S3.3, Activation treatment: Activate the cleaned copper foil with a dilute sulfuric acid solution to make the copper foil surface more reactive; S4. Nanoparticle deposition on metal substrates: S4.
1. Preparation of electrolyte: prepare 0.05 mol / L silver nitrate electrolyte to make the electrolyte composition uniform and stable; S4.2, electrochemical deposition parameter setting: control the current density, the deposition time is 15 minutes; S4.3, Nanoparticle formation: Through electrochemical deposition, uniformly distributed, fine-sized silver nanoparticles are formed on the surface of the copper foil, which significantly increases the surface roughness of the metal substrate and provides more contact sites; S5. Composite of graphene and metal substrate: S5.
1. Graphene suspension spraying: using high-precision spray equipment, the pre-treated graphene suspension is evenly sprayed on the metal substrate; S5.2, forming an interface enhancement layer: forming an interface enhancement material layer on the graphene layer by spin coating, wherein the interface enhancement material layer is made of a solution containing a nano-scale silane coupling agent to improve its bonding strength; S5.3, Drying treatment: Place the sprayed sample in a drying oven to remove the solvent so that the graphene is firmly attached to the metal substrate; S5.4, low temperature hot pressing composite: using hot pressing equipment, under the protection of nitrogen, the graphene is brought into close contact with the metal substrate, physical and chemical interactions occur, and a strong bonding interface is formed; S6. Post-processing: S6.1 Annealing: Anneal the composite gasket in a vacuum annealing furnace with a vacuum degree of 10 -3 Pa, annealing temperature is 400℃, time is 1 hour. During the annealing process, the diffusion and rearrangement of atoms can eliminate the residual stress inside the material; S6.
2. Anti-oxidation coating: Silicon nitride is selected as the anti-oxidation coating material, and the coating method is sprayed to control the thickness of the coating to 5μm to prevent the gasket from oxidation and corrosion in harsh environments and extend its service life.
2. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: The organic solvent selected in S1.1 is N-methylpyrrolidone NMP, and the surfactant is sodium dodecylbenzene sulfonate, and the concentration thereof is controlled at 2 wt %.
3. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: S1.2: 10 g of high-quality graphite powder is uniformly dispersed in 1000 ml of N-methylpyrrolidone (NMP) solution containing 5 wt% sodium dodecylbenzene sulfonate, and ultrasonically treated at a frequency of 20 kHz and 40 W / cm 2 The ultrasonic treatment is performed with an amplitude of 1000 nm and the ultrasonic time is 3-6 hours to fully exfoliate the graphite powder into graphene sheets.
4. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: The S2.1 performs plasma treatment on the obtained graphene to introduce active functional groups on its surface. The treatment gas is a mixed gas of argon and oxygen with a volume ratio of 9:
1. During the treatment, the plasma power is controlled at 200 W and the treatment time is 15 minutes. The high-energy particles of the plasma bombard the graphene surface to produce chemically active sites, thereby enhancing the compatibility with the metal and laying the foundation for subsequent good bonding with the metal.
5. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: The plasma treatment of the S2 graphene further comprises: S2.5, Plasma excitation method: A unique plasma excitation method, namely pulse power excitation, is used to generate more active plasma, making the interaction between plasma and graphene more intense, thereby improving the effect of surface modification; S2.
6. Multi-stage plasma treatment: Design a multi-stage plasma treatment process and adjust the gas ratio, power and treatment time parameters at different stages.
6. The method for preparing a graphene metal thermally conductive pad according to claim 5, characterized in that: The specific parameters of different stages of the S2.6 multi-stage plasma treatment are adjusted as follows: The first stage, pretreatment: the gas volume ratio of argon and oxygen was set to 8:2, the power was set to 100W, and the treatment time lasted for 5 minutes to perform preliminary activation on the graphene surface; The second stage, deep treatment: the gas volume ratio of argon and oxygen is adjusted to 9:1, the power is adjusted to 150W, and the treatment time is extended to 7 minutes to introduce more active functional groups to make the graphene surface active and compatible with metals; The third stage is stabilization treatment: the gas ratio of argon and oxygen is maintained at 9:1, the power is reduced to 120W, and the treatment time lasts for 5 minutes. The stabilization treatment is used to consolidate the effect of surface modification and ensure the stable existence of active functional groups, while avoiding adverse effects of excessive treatment on the graphene structure.
7. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: The S3.1 uses high-purity copper foil as the metal substrate, performs surface cleaning on the copper foil, and uses acetone, ethanol and deionized water for ultrasonic cleaning in sequence. The ultrasonic cleaning time of each solvent is 15 minutes. The cleaned copper foil is activated using a 5% dilute hydrochloric acid solution for 10 minutes to make the copper foil surface have higher reactivity.
8. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: During the nanoparticle deposition process of the S4 metal substrate, a layer of nanoscale metal particles is deposited on the surface of the copper foil by an electrochemical method, using a 0.05-0.1 mol / L silver nitrate electrolyte and controlling the current density to 0.1-0.5 A / dm 2 The deposition time is 25 minutes, and uniformly distributed, small-sized silver nanoparticles are formed on the surface of the copper foil. These nanoparticles can increase the surface roughness of the metal substrate, thereby providing more contact sites and increasing the contact area with graphene.
9. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: The S5 evenly sprays the pretreated graphene suspension on the metal substrate, using high-precision spray equipment to control the spray pressure to 0.3MPa, the flow rate to 5ml / min and the angle to 45°, so that the graphene suspension can evenly cover the surface of the metal substrate, and the sprayed sample is placed in a drying oven for drying, the drying temperature is controlled at 100°C, and the drying time is 2 hours to remove the solvent, so that the graphene is firmly attached to the metal substrate.
10. The method for preparing a graphene metal thermally conductive pad according to claim 1, characterized in that: The S5.4 adopts a low-temperature hot pressing process to composite the graphene with the metal substrate under the protection of an inert gas. During the hot pressing process, high-purity nitrogen is introduced to prevent the graphene and the metal from oxidizing at high temperatures. The pressure is controlled at 10 MPa. By applying pressure uniformly, the graphene is brought into close contact with the metal substrate. The temperature is controlled at 250°C for 1.5 hours.
Citation Information
Cited By
Preparation method of high-heat-transfer graphite-based interface material
CN121798987A
Preparation method of high-pass heat graphite-based interface material
CN121798987B